UNIVERSAL DESIGN FOR LEARNING IN HYBRID EDUCATION: BRIDGING ACCESSIBILITY AND ACADEMIC ACHIEVEMENT - Ni Wayan Karimi; Putri Julia Ningsi; Nina Anis; Dyah Retno Wulan (Journal Neosantara Hybrid Learning, 2026)
The integration of Universal Design for Learning (UDL) in hybrid education has gained attention for its potential to address the diverse needs of students and bridge gaps in accessibility and academic achievement. Hybrid learning, which combines in-person and online instruction, presents unique challenges in ensuring equal access to learning resources and opportunities. UDL, with its flexible framework for creating inclusive educational environments, aims to provide multiple means of representation, engagement, and expression. This study investigates the impact of UDL principles on student engagement and academic performance in hybrid learning settings. The research employs a mixed-methods approach, combining quantitative surveys and academic performance assessments with qualitative interviews and focus groups. The results indicate that UDL significantly enhances student engagement and academic achievement in hybrid courses, with a 15% improvement in test scores and higher participation rates. Students reported increased satisfaction, particularly due to the adaptability of learning materials and assessments. The study concludes that UDL offers a promising framework for improving accessibility and promoting academic success in hybrid education. Implementing UDL principles can help educators create more inclusive and equitable learning environments, fostering greater success for a diverse range of students.